Block amorphous material with ultrahigh magnetocaloric performance and preparation method thereof

Through Fluxing purification technology and copper mold spray casting technology, Fe82P12C6 bulk amorphous alloy without rare earths and boron was prepared, solving the shortcomings of existing iron-based amorphous alloys in terms of magnetothermal properties, amorphous formation capabilities and costs. Low-cost iron-based amorphous alloy with high magnetic entropy variable value and large refrigeration capacity is achieved.

CN119491172APending Publication Date: 2025-02-21HEBEI UNIV OF TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411688369.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

The existing iron-based amorphous alloys have shortcomings in magnetothermal properties, amorphous formation ability and cost, especially containing expensive rare earth elements and boron elements, and have poor amorphous formation ability, making it difficult to prepare large-sized amorphous alloys.

Method used

Using Fluxing purification technology and copper mold spray casting technology, Fe82P12C6 bulk amorphous alloy without rare earths and boron is prepared by using common Fe, P and C elements in nature, which improves the amorphous formation ability and magnetothermal properties of the material. .

Benefits of technology

Iron-based amorphous alloy with low cost, high magnetic entropy variable value and large refrigeration capacity has a magnetic entropy variable value of 7.9 J/(kg K) at 5 T, and a refrigeration capacity of 438 ~ 472 J/kg, and can Prepare large-sized bulk amorphous alloys.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119491172A_ABST
    Figure CN119491172A_ABST
Patent Text Reader

Abstract

The invention relates to a bulk amorphous material with ultrahigh magnetocaloric performance and a preparation method thereof. The component of the bulk amorphous material is FeaPbCc, a, b and c are atomic percentages, and a is more than or equal to 80 and less than or equal to 82, b is more than or equal to 11 and less than or equal to 14, x is more than or equal to 6 and less than or equal to 9, and a + b + c = 100. In the preparation process, an alloy ingot is purified by using a Flux technology, the amorphous forming ability of the material is improved, and then the FePC block amorphous alloy is prepared by using a copper mold spray casting technology. The saturation magnetization intensity of the amorphous material is 1.51 to 1.64 T; when the external magnetic field is 5 T, the magnetic entropy change value is 5.9-7.9 J / (kg K), and the refrigerating capacity is 438-472 J / kg; the three common elements Fe, P and C in the nature are adopted, the price is low, the cost is greatly reduced, and the ternary iron-based bulk amorphous alloy with the excellent magnetocaloric performance is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of amorphous magnetocaloric materials, and in particular to a bulk amorphous alloy with ultra-high magnetocaloric properties and a preparation method thereof. Background Art

[0002] The magnetocaloric effect is a reversible temperature change phenomenon that occurs during the adiabatic magnetization and demagnetization of magnetic materials. This phenomenon was first discovered by Weiss and Piccard in Ni in 1917. The magnetocaloric effect can control the ambient temperature through the heat absorption and heat release process of magnetic materials under a changing magnetic field. Magnetic materials based on the magnetocaloric effect can not only be used in the field of magnetic refrigeration, such as low-temperature liquid hydrogen storage, room temperature household refrigerators, air conditioners, and automotive air conditioners, but can also be used in the medical field, such as the delivery and release of targeted drugs, and thermal therapy for cancer treatment. In addition, the magnetocaloric effect of materials can also be used in the recycling and reuse of industrial waste heat, the precise control of temperature in high-temperature environments, such as high-temperature reactors, semiconductor manufacturing equipment, and the temperature adjustment of satellites and space probes. In summary, if magnetic materials based on the magnetocaloric effect are to be better applied, the materials need to have excellent magnetocaloric properties, such as large magnetic entropy change and refrigeration capacity.

[0003] Crystalline materials usually have a large magnetic entropy change, such as Gd-Si-Ge [Nature 429 (2004) 853-857], Ni-Mn-Ga [J. Alloys Compd., 944 (2023) 169196], La-Fe-Si [Appl. Phys. Lett. 81 (2002) 1276], etc. These materials belong to the first-order phase change, with a sharp and narrow magnetic entropy change curve, a narrow application temperature range, and a lower refrigeration capacity. Secondary phase change materials such as crystalline Gd and amorphous alloys have the characteristics of wide working temperature range and large refrigeration capacity, which are more conducive to practical applications. However, most of the amorphous alloys with excellent magnetocaloric properties are rare earth-based amorphous alloys. The challenges of Gd and rare earth-based amorphous alloys in practical applications are high cost, easy corrosion, high brittleness and difficulty in processing. Therefore, it is particularly urgent and important to develop an amorphous alloy with low cost, good toughness, high magnetic entropy change and large refrigeration capacity.

[0004] Iron-based amorphous alloys have attracted widespread attention due to their low cost and good soft magnetic properties. Generally speaking, iron-based amorphous alloys have low magnetic entropy change values. Most studies have improved the magnetocaloric properties of materials by doping rare earth elements into iron-based amorphous alloys, such as Fe 87 Pr 11 B 2 [Intermetallics 172 (2024) 108394], Fe 88 Zr4 Nd 4 B 4 [J.Non-Cryst. Solids 611 (2023) 122347] and Fe 88 Zr 2 Ti 2 Nd 3 Pr 1 B 4 [J. Non-Cryst. Solids636 (2024) 122989] amorphous alloys, etc. Although the maximum magnetic entropy change values ​​of these iron-based amorphous alloys at 5 T are all higher than 4J / (kg K), which is close to the maximum magnetic entropy change value of GdCo-based amorphous alloys. However, these materials contain expensive rare earth elements and boron elements and have poor amorphous forming ability. They can only be prepared into small-sized amorphous thin strips using copper roller stripping technology, which is not suitable for processing and manufacturing. Summary of the invention

[0005] Aiming at the deficiencies of the iron-based amorphous alloy in the prior art in terms of magnetocaloric properties, amorphous forming ability and cost, the purpose of the present invention is to provide a method for preparing an iron-based bulk amorphous alloy which does not contain expensive rare earth elements and boron elements and has ultra-high magnetocaloric properties. By utilizing the Fluxing purification technology, the amorphous forming ability of the material is improved, and the technical idea of ​​preparing large-sized amorphous alloys is realized. The FePC bulk amorphous alloy is prepared by copper mold spray casting technology, and finally a low-cost Fe with excellent magnetocaloric properties is successfully prepared. 82 P 12 C 6 Bulk amorphous alloy. The present invention uses three common elements of Fe, P and C in nature, which are low in price and greatly reduce the cost. The obtained ternary iron-based amorphous alloy has excellent magnetocaloric effect.

[0006] The present invention achieves the above object through the following technical solutions: A bulk amorphous material with ultra-high magnetocaloric properties, the bulk amorphous material comprising Fe a P b C c , where a, b, and c are atomic percentages and satisfy 80 ≤ a≤ 82, 11 ≤ b ≤ 14, 6 ≤ x ≤ 9, and a + b + c = 100.

[0007] The size of the FePC bulk amorphous alloy is 1 to 2 mm.

[0008] The saturation magnetization is 1.51 ~ 1.64 T; When the external magnetic field is 5 T, the magnetic entropy change is 5.9 ~ 7.9 J / (kg K) and the cooling capacity is 438 ~ 472 J / kg.

[0009] The method for preparing a bulk amorphous material with ultra-high magnetocaloric properties comprises the following steps: (1) Pure Fe particles, Fe 3 P and C blocks are composed of Fe a P b C c Atomic percentage configuration of raw materials in; Among them, pure Fe particles, Fe 3 The purity of P and C is greater than or equal to 99 wt.%.

[0010] (2) placing the raw materials prepared in step (1) in a high-frequency induction melting furnace, evacuating the furnace, and melting the raw materials in an argon protective atmosphere. After melting, pouring the raw materials into a copper mold and cooling the mold to obtain a master alloy ingot. (3) grinding the master alloy ingot in step (2) to remove surface impurities, cutting it into small pieces with a mass of 2.0 to 3.0 g, and then ultrasonically cleaning it in anhydrous ethanol; (4) placing the small alloy pieces obtained in step (3) together with calcium oxide and boron oxide powders in a quartz tube, evacuating the tube, and melting the tube in a high-temperature furnace at 1000 to 1400°C for 2 to 4 hours. The molten alloy is purified for a long time under the wrapping of the oxide melt. After the purification is completed, the alloy is taken out and ultrasonically cleaned for later use. The mass ratio of calcium oxide to boron oxide powder is 1:3.5 to 1:6; the mass ratio of alloy to boron oxide is 1:1 to 1:1.5; (5) The small piece of alloy obtained in step (4) is placed in a quartz tube with a small hole at the bottom. After evacuation, the molten alloy is sprayed into a copper mold using gas pressure difference under argon atmosphere to obtain a bulk amorphous alloy.

[0011] The vacuum degree of the evacuation in steps (2) and (5) of the above preparation method is 2 to 5 x 10 -3 Pa; The small opening at the lower end of the quartz tube in step (5) is about 0.8 to 1 mm, and the injection pressure difference is 0.075 to 0.095 MPa.

[0012] The essential features of the present invention are: The material composition of the present invention is simple, with only three elements, Fe, P, and C, which are all common elements in nature, and no rare earth and boron elements (rare earth elements are expensive and difficult to mine, and the presence of boron elements will cause the brittleness of the material, which is not conducive to processing); secondly, in terms of the preparation method, compared with the traditional smelting and throwing belt technology, the purification technology of the alloy ingot is added, and the molten alloy is completely wrapped by the molten oxide in the Fluxing purification technology, which can effectively prevent contact with external gas and prevent alloy oxidation; furthermore, the molten Fluxing medium can absorb oxide impurities and other heterogeneous nucleation impurities in the alloy, and improve the amorphous forming ability of the alloy; the alloy is in a molten state for a long time, and the component distribution is more uniform. The present invention increases the amorphous forming ability of the material, and can prepare a large-sized bulk amorphous alloy by using the copper mold spray casting method.

[0013] The beneficial effects of the present invention are: (1) Most of the iron-based amorphous alloys with excellent magnetocaloric properties found so far contain expensive rare earth elements and boron elements, and the addition of rare earth elements and boron elements will cause the brittleness of the material and increase the cost of the material. The present invention uses three elements commonly found in nature, Fe, P and C, which are low in price and greatly reduce the cost.

[0014] (2) The iron content of the Fe-based amorphous alloys with excellent magnetocaloric effect reported so far mostly exceeds 85 at.%. The higher the iron content, the worse the amorphous forming ability of the material. The present invention controls the iron content within 82 at.%, rationally regulates the composition of FePC, and at 5 T, Fe 82 P 12 C 6 The magnetic entropy change value of amorphous alloy is increased to 7.9 J / (kg K), which is higher than that of traditional Fe 87 Pr 11 B 2 The magnetic entropy change value of the amorphous ribbon is 40% of that of the ternary iron-based amorphous alloy (4.73 J / (kg K)), making it the alloy with the highest magnetic entropy change value currently.

[0015] (3) Most iron-based amorphous alloys have poor amorphous forming ability and can only synthesize amorphous thin strips with a thickness of 20-50 μm, which is not conducive to processing and manufacturing. The present invention uses Fluxing technology to purify the alloy ingots and uses copper mold spray casting technology to successfully prepare amorphous rods with a diameter of 1-2 mm.

[0016] (4) The Fluxing purification technology of the present invention can effectively remove impurities from the alloy ingot, greatly improving the amorphous forming ability of the material.

[0017] (5) After the alloy ingot is purified by Fluxing, large-sized bulk amorphous alloys can be prepared by controlling the injection pressure difference in the copper mold spray casting technology and melting the alloy melt for an appropriate time. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 This is a physical picture of the FePC amorphous rod in Example 1; Figure 2 is the XRD pattern of the FePC bulk amorphous alloy in Examples 1 to 2; Figure 3 is the DSC curve of the FePC bulk amorphous alloy in Examples 1 to 2; Figure 4 The maximum magnetic entropy change curve of FePC bulk amorphous alloy in Example 2 is changed with the magnetic field; Figure 5 This is the curve of the refrigeration capacity of the FePC bulk amorphous alloy changing with the magnetic field in Example 2. DETAILED DESCRIPTION

[0019] The present invention is further described in detail with reference to the following examples and accompanying drawings.

[0020] Example 1: Fe 80.7 P 12.3 C 7 Preparation of bulk amorphous alloys This example uses the Fluxing purification technology and copper mold spray casting method to prepare Fe with a diameter of 1.5 mm. 80.7 P 12.3 C 7 Bulk amorphous alloys.

[0021] Step 1: Mix 99.9 wt.% pure Fe and 99.7 wt.% pure Fe 3 P and 99.9wt.% pure C block according to atomic percentage Fe 80.7 P 12.3 C 7 Weigh the raw materials and put them into the boron nitride crucible of the high-frequency induction melting furnace and evacuate to 4 x 10 -3 Pa, high-purity argon gas with a purity of 99.9% is filled into the cavity until the pressure in the melting furnace is -0.6 MPa, and the raw materials are melted by heating with a high-frequency induction coil. The melting temperature is 1900 °C, and the total mass of the raw materials is 15g. The melting speed of the raw materials is accelerated by shaking the melting crucible, and the alloy is kept in a molten state in the crucible for 30 min to ensure that the alloy composition is uniform. The molten alloy is quickly poured into a copper crucible and cooled to obtain a master alloy ingot; Step 2: Grind the surface of the master alloy obtained in step 1 to remove the oxide scale, cut it into small pieces with a mass of about 2.5 g, and ultrasonically clean it in anhydrous ethanol for 5 minutes, blow dry it and set it aside; Step 3: The obtained alloy block with a mass of 2.5 g was placed in a quartz tube together with 2.5 g of boron oxide and 0.6 g of calcium oxide powder and evacuated to 5 x 10 -2 Pa, and then put it into a high-temperature furnace and heat it until the alloy and oxide are completely melted. The melting temperature is 1300°C. The molten alloy is wrapped by the oxide melt medium and kept in the molten state for 2 hours. After the Fluxing purification is completed, the alloy is taken out and ultrasonically cleaned for use.

[0022] Step 4: The Fe obtained in step 3 80.7 P 12.3 C 7 The small alloy block was placed in a quartz tube with a small hole at the bottom. The diameter of the hole was 0.9 mm and the vacuum was evacuated to 2 x 10 -3 Pa, fill an appropriate amount of high-purity argon into the cavity, heat and melt it using a high-frequency induction coil, keep it in a molten state for 1 min, and then spray it into a copper mold with high-purity argon to obtain a bulk amorphous alloy. The experimental parameters used in the present invention are: the copper mold aperture is 1.5 mm, the injection pressure difference is 0.085 MPa; Example 1 Preparation of Fe 80.7 P 12.3 C 7 The appearance of amorphous rod is as follows Figure 1 The X-ray diffraction (XRD) pattern of the alloy rod is shown in Figure 2 As shown in the figure, the diffuse broad diffraction peaks are shown, indicating that the alloy rod is a completely amorphous structure; the DSC curve of the bulk amorphous is tested by differential scanning calorimetry, as shown in Figure 3 As shown in the figure, the thermodynamic parameters are determined. The Curie temperature of the amorphous rod is 583 K, and the initial crystallization temperature T x The magnetic field of Fe is 696 K and the liquidus temperature is 1283 K. The magnetization curves of amorphous rods at different temperatures near the Curie temperature were tested using a comprehensive physical property measurement system (PPMS). The maximum applied magnetic field was 5 T. 80.7 P 12.3 C 7 The maximum magnetic entropy change of the amorphous rod at 5 T is 5.9 J / (kg K), and the cooling capacity is 472 J / kg.

[0023] Example 2: Fe 82 P 12 C 6 Preparation of bulk amorphous alloys This example uses the Fluxing purification technology and copper mold spray casting method to prepare Fe with a diameter of 1 mm.82 P 12 C 6 Bulk amorphous alloys.

[0024] Step 1: Mix 99.9 wt.% pure Fe and 99.7 wt.% pure Fe 3 P and 99.9wt.% pure C block according to atomic percentage Fe 82 P 12 C 6 Weigh the raw materials and put them into the boron nitride crucible of the high-frequency induction melting furnace and evacuate to 5 x 10 -3 Pa, high-purity argon gas with a purity of 99% is filled into the cavity until the pressure in the furnace cavity is -0.6 MPa, and a high-frequency induction coil is used to heat and melt 15g of raw materials at a melting temperature of 1850°C. The melting speed of the raw materials is accelerated by shaking the melting crucible, and the alloy is kept in a molten state in the crucible for 25 minutes to ensure uniform alloy composition. The molten alloy is quickly poured into a copper crucible for cooling to obtain a master alloy ingot; Step 2: Grind off the surface oxide layer of the master alloy obtained in step 1, cut into small pieces with a mass of about 2.5 g, and ultrasonically clean them in anhydrous ethanol for 5 min, blow dry and set aside; Step 3: The obtained alloy block with a mass of 2.5 g was placed in a quartz tube together with 2.5 g of boron oxide and 0.6 g of calcium oxide powder and evacuated to 5 x 10 -2 Pa, and then put it into a high-temperature furnace and heat it until the alloy and oxide are completely melted. The molten alloy is wrapped by the oxide melt medium and kept in a molten state for 4 hours. The melting temperature is 1300℃. After the Fluxing purification is completed, the alloy is taken out and ultrasonically cleaned for use; Step 4: The Fe obtained in step 3 82 P 12 C 6 The small alloy block was placed in a quartz tube with a small hole at the bottom. The diameter of the hole was 1 mm and the vacuum was evacuated to 3 x 10 -3 Pa, fill a proper amount of high-purity argon into the cavity, heat and melt it using a high-frequency induction coil, keep the molten state for 1 min, and then spray it into the copper mold with high-purity argon to obtain a bulk amorphous alloy. The experimental parameters used in the present invention are: the copper mold aperture is 1 mm, and the spray pressure difference is 0.09 MPa.

[0025] Example 2 Preparation of Fe 82 P 12 C 6 The appearance of bulk amorphous alloys is similar to Figure 1 Shown is a rod with a diameter of 1 mm.

[0026] The X-ray diffraction (XRD) pattern of the alloy strip is shown in Figure 2 As shown, the figure shows a diffuse broad diffraction peak, indicating that the bulk amorphous alloy is a completely amorphous structure; The DSC curve was tested by differential scanning calorimetry. Figure 3 As shown, the DSC curve shows two obvious exothermic peaks related to crystallization and one endothermic peak related to melting. 82 P 12 C 6 The Curie temperature of bulk amorphous alloy is 579 K, and the initial crystallization temperature T x The liquefaction temperature is 662 K and 1300 K, showing high thermal stability; Fe was measured using a comprehensive physical property measurement system (PPMS) 82 P 12 C 6 The magnetization curves of bulk amorphous alloys at different temperatures near the Curie temperature are analyzed to obtain Fe 82 P 12 C 6 Magnetocaloric properties of bulk amorphous alloys. At 2 T and 5 T, Fe 82 P 12 C 6 The maximum magnetic entropy change values ​​of bulk amorphous alloys are 3.6 J / (kg K) and 7.9 J / (kg K) respectively. Figure 4 ), the cooling capacity is 152 J / kg and 438 J / kg respectively ( Figure 5 ), the magnetic entropy change value of this alloy is the highest value among the iron-based amorphous alloys reported so far.

[0027] In summary, the FePC bulk amorphous alloy with ultra-high magnetocaloric performance prepared by the present invention exhibits the following advantages: 1. Simple composition: Avoids the use of expensive rare earth and boron elements, effectively reducing the cost of materials; 2. Fluxing purification technology: The present invention utilizes molten oxides to purify the alloy ingots, thereby improving the amorphous forming ability of the material and preparing a bulk amorphous alloy, which is suitable for processing and preparation, and provides convenience for customized production of materials; 3. Ultra-high magnetocaloric performance: FePC bulk amorphous alloy exhibits ultra-high magnetic entropy change value and large refrigeration capacity, which improves the efficiency of the material in practical applications.

[0028] Matters not covered by the present invention are known technologies.

Claims

1. A bulk amorphous material with ultra-high magnetocaloric properties, characterized by The composition of the bulk amorphous is Fe a P b C c , where a, b, and c are atomic percentages and satisfy 80 ≤ a≤ 82, 11 ≤ b ≤ 14, 6 ≤ x ≤ 9, and a + b + c = 100.

2. The bulk amorphous material with ultra-high magnetocaloric properties according to claim 1, characterized in that The size of the FePC bulk amorphous alloy is 1 to 2 mm.

3. The bulk amorphous material with ultra-high magnetocaloric properties according to claim 1, characterized in that The saturation magnetization of the amorphous material is 1.51~1.64 T; When the external magnetic field is 5 T, the magnetic entropy change is 5.9 ~ 7.9 J / (kg K) and the cooling capacity is 438 ~ 472 J / kg.

4. The method for preparing a bulk amorphous material with ultra-high magnetocaloric properties according to claim 1, characterized in that the method comprises the following steps: (1) Pure Fe particles, Fe3P and C blocks are divided into a P b C c Atomic percentage configuration of raw materials in; (2) placing the raw materials prepared in step (1) in a high-frequency induction melting furnace, evacuating the furnace, and melting the raw materials in an argon protective atmosphere. After melting, pouring the raw materials into a copper mold and cooling the mold to obtain a master alloy ingot. (3) grinding the master alloy ingot in step (2) to remove surface impurities, cutting it into blocks, and then ultrasonically cleaning it in anhydrous ethanol; (4) placing the bulk alloy obtained in step (3) together with calcium oxide and boron oxide powder in a quartz tube, evacuating the tube, and melting the tube in a high-temperature furnace at 1000 to 1400°C for 2 to 4 hours. The molten alloy is purified for a long time under the wrapping of the oxide melt. After the purification is completed, the alloy is taken out and ultrasonically cleaned for use; The mass ratio of calcium oxide to boron oxide powder is 1:3.5 to 1:6; the mass ratio of alloy to boron oxide is 1:1 to 1:1.5; (5) The small piece of alloy obtained in step (4) is placed in a quartz tube with a small hole at the bottom. After evacuation, the molten alloy is sprayed into a copper mold under an argon atmosphere to obtain a bulk amorphous alloy.

5. The method for preparing a bulk amorphous material with ultra-high magnetocaloric properties as claimed in claim 4, characterized in that the purity of pure Fe particles, Fe3P and C are greater than or equal to 99 wt.%.

6. The method for preparing a bulk amorphous material with ultra-high magnetocaloric properties as claimed in claim 4, characterized in that The vacuum degree of the evacuation in steps (2) and (5) of the above preparation method is 2 to 5 x 10 -3 Pa.

7. The method for preparing a bulk amorphous material with ultra-high magnetocaloric properties as claimed in claim 4, characterized in that The size of the small opening at the lower end of the quartz tube in step (5) is 0.8 ~ 1 mm, and the injection pressure difference is 0.075 ~ 0.095 MPa.

8. The method for preparing a bulk amorphous material with ultra-high magnetocaloric properties as claimed in claim 4, characterized in that The mass of the block in step (3) is 2.0 ~ 3.0 g.

Citation Information

Patent Citations

  • Oxygen-controllable iron-based magnetic refrigeration alloy and preparation method thereof

    CN111748754A

  • Bulk rare earth-based high-entropy amorphous alloy with high magnetothermal effect and preparation method of bulk rare earth-based high-entropy amorphous alloy

    CN117702011A

  • Centimeter-level High-strength Iron-based Bulk Amorphous Alloy and Novel Copper Mold Casting Method Thereof

    US20200332404A1